Legal Aspects Of Oil Palm Theft In Rantau Prapat Jurisdiction - Ariman Sitompul (International Asia Of Law and Money Laundering, 2023)
The crime of theft is regulated in Article 362 of the Criminal Code (KUHP) which states that anyone who takes goods, wholly or partly belonging to another person, with the intention of possessing the goods against the law, shall be punished for stealing with imprisonment for a maximum of five years or a fine of as much as nine thousand rupiah, but in practice there is still a crime of oil palm theft in the rantau prapat area which is the city of dollar. The purpose of writing is to explain the causes of the crime of oil palm theft in the jurisdiction of rantau prapat, to explain the efforts to resolve oil palm theft in the jurisdiction of rantau prapat. Data obtained from the results of field research as well as data from the results of literature research, secondary Data is done by reading and analyzing legislation, books, and articles related to this research. Field research was conducted to obtain primary data through interviews with respondents and informants.analyzed using a qualitative approach. the preparation of research results is carried out using a descriptive method that is trying to give a real picture of the realities found in practice by describing the results of field research accompanied by a description of the applicable legal basis. The results of the study into the causes of oil palm theft in the jurisdiction of rantau prapat are economic factors, factors of opportunity, and factors of land disputes. Efforts to combat oil palm theft in the jurisdiction of rantau prapat have been carried out by preventive or preventive means, namely installing sheets on prohibitions and sanctions for those who steal oil palm both community and company property on Village information boards, then the police will make a reperesive effort, namely enforcement, arrest after receiving reports from the community. It is hoped that all authorities can work together and a sense of concern and resolution of land disputes for people living in the area of the company both from the government and the company in order to reduce the crime of oil palm theft in the jurisdiction of rantau prapat.